Reorientasi Pidana Ganti Rugi: Analisis Ekonomi Hukum Terhadap Inefisiensi Subsidair Kurungan - Fathin Abdullah; Rifka Safira; Naqia Annisa Faradiz (Indonesian Journal Publisher, 2026)
This study aims to analyse the inefficiencies of the compensation mechanism in the Indonesian criminal justice system, which often converts financial obligations into alternative imprisonment (subsidiary). The research employed a normative legal method with legislative, case law, and economic approaches, utilising Richard Posner and Gary Becker's efficiency theories. The findings indicate that converting compensation into custodial sentences creates a systemic double loss. This mechanism results in a deadweight loss where victims remain materially uncompensated for their medical and psychological costs, while the state simultaneously bears the fiscal burden of detaining the offender in an already overcrowded prison system. Based on the analysis of Supreme Court Decision No. 1149 K/Pid/2022, Law No. 1 of 2023 (National Criminal Code), and Law No. 12 of 2022 (Law on Sexual Violence Crimes), this study concludes that alternative imprisonment is an inefficient instrument that degrades the victim's dignity. Therefore, this research recommends that asset recovery through early asset seizure and income garnishment must be enforced as a top priority to achieve genuine, victim-centered restorative justice.